2020
DOI: 10.22146/jsv.54190
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Bunting dan Laktasi Terhadap Hematologi dan Mineral Kambing Peranakan Ettawa di Kulonprogo, Yogyakarta, Indonesia

Abstract: The effects of pregnancy and lactation on hematochemical and mineral parameters were evaluated in Ettawa cross-bred goats in Disctrict Kulonprogo, Yogyakarta, Indonesia. Blood plasma samples were collected from 14 th pregnant goats (2 month n=4; 3 month n=6; 4 month n=4) and 16 lactation goats (1 month, n= 4; 2 month, n=5; 3 month, n=3 and 4 month, n=4). Blood serum samples were collected from 18 pregnanct goats (1 month, n=3; 2 month, n=2; 3 month, n=6; 4 month, n=4) and 16 lactation goats (1 month, n=4; 2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This could be because the sampling in both studies was carried out randomly without considering the age of need and the duration of lactation experienced by the ewes. However, in a study conducted by Sarmin et al, [9] on PE goats, found that the fourth-month pregnant female had an N/L ratio of 2.89 ± 2.89 and a fourth-month lactation of 0.74 ± 0.55, in line with the research that has been done. According to Kanna et al, [10], the N/L ratio can indicate stress when it exceeds 1.5.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…This could be because the sampling in both studies was carried out randomly without considering the age of need and the duration of lactation experienced by the ewes. However, in a study conducted by Sarmin et al, [9] on PE goats, found that the fourth-month pregnant female had an N/L ratio of 2.89 ± 2.89 and a fourth-month lactation of 0.74 ± 0.55, in line with the research that has been done. According to Kanna et al, [10], the N/L ratio can indicate stress when it exceeds 1.5.…”
Section: Resultssupporting
confidence: 56%
“…In this study, pregnant conditions can trigger an increase in neutrophils caused by a decrease in immunity, so that the mother is more susceptible to infection. Research conducted by Sarmin et al, [9] found that the value of the N/L ratio in pregnant women at the final gestational age increased from the previous month. This can be caused by the rapid development of the fetus, the growing size of the fetus and the rapid growth of the mammary glands [17].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It can occur due to the influence of the lactose content in the egg yolk, which plays a role in helping to remove water from the cells so that it can help prevent the formation of ice crystals, which can reduce the motility of spermatozoa during the freezing process [41]. The addition of red galangal extract, which contains antioxidants, can reduce levels of free radicals resulting from metabolic processes, so that damage to spermatozoa can be minimized and semen quality can be maintained [37].…”
Section: Issn 2087-2852 E-issn 2338-1655mentioning
confidence: 99%
“…Beberapa parameter komponen darah berubah saat ternak bunting mengikuti perubahan metabolisme yang terjadi pada kondisi bunting. Penelitian perubahan metabolik selama kebuntingan dan periode laktasi pada ternak telah dilaporkan pada kambing Alphine, kambing Peranakan Ettawa (Sarmin et al, 2020), kambing Nguni, Boer, dan Non-Descript di Afrika Selatan (Idamokoro et al, 2018), keledai (Bonelli et al, 2016), sapi Bali (Kendran & Pemayun, 2020), domba Creole (Cuadrado et al, 2019), domba Morada Nova dan Santa Ines (Bezzera et al, 2017). Hasil-hasil penelitian tersebut menunjukkan adanya variasi metabolit pada saat bunting dan periode laktasi pada masing-masing hewan.…”
Section: Pendahuluanunclassified